LGBT inclusion at the workplace - Ismail, Fadillah; Tiew, Wen Li; Ali Hassan Humaid Alhosani, Adnan; Lee, Te Chuan (Penerbit UTHM, 2020)
LGBT represent to lesbian, gay, bisexual and transgender (Picture 1). These are the terms used to describe people's gender identity and sexual orientation. One's gender identify means that no matter one feels female, male or bisexual; no matter one's biological sex. Sexual orientation refer to an often enduring pattern of emotive, romantic or sexual attractions to men, women, or multi-genders. For example, heterosexual (men and women), homosexual (men and men/ women and women) or bisexual (both sexes).